Online Advertising to Reach and Recruit Latino Smokers to an Internet Cessation Program: Impact and Costs - Graham, Amanda L; Fang, Ye; Moreno, Jose L; Streiff, Shawn L; Villegas, Jorge; Muñoz, Ricardo F; Tercyak, Kenneth P; Mandelblatt, Jeanne S; Vallone, Donna M (JMIR Publications, 2012)
BackgroundTobacco cessation among Latinos is a public health priority in the United States, particularly given the relatively high growth of this population segment. Although a substantial percentage of American Latinos use the Internet, they have not engaged in Web-based cessation programs as readily as other racial/ethnic subgroups. A lack of culturally specific advertising efforts may partly explain this disparity. ObjectivePhase I of this study focused on the development of four Spanish-language online banner advertisements to promote a free Spanish-language smoking cessation website (es.BecomeAnEX.org). Phase II examined the relative effectiveness of the four banner ads in reaching and recruiting Latino smokers to the cessation website. MethodsIn Phase I, 200 Spanish-speaking Latino smokers completed an online survey to indicate their preference for Spanish-language banner ads that incorporated either the cultural value of family (familismo) or fatalism (fatalismo). Ads included variations on message framing (gain vs loss) and depth of cultural targeting (surface vs deep). In Phase II, a Latin square design evaluated the effectiveness of the four preferred ads from Phase I. Ads were systematically rotated across four popular Latino websites (MySpace Latino, MSN Latino, MiGente, and Yahoo! en Español) over four months from August to November 2009. Tracking software recorded ad clicks and registrants on the cessation website. Negative binomial regression and general linear modeling examined the main and interacting effects of message framing and depth of cultural targeting for four outcomes: number of clicks, click-through rate, number of registrants, and cost per registrant. ResultsIn Phase I, smokers preferred the four ads featuring familismo. In Phase II, 24,829,007 impressions were placed, yielding 24,822 clicks, an overall click-through rate of 0.10%, and 500 registrants (2.77% conversion rate). Advertising costs totaled US $104,669.49, resulting in an overall cost per click of US $4.22 and cost per registrant of US $209.34. Website placement predicted all four outcomes (all P values < .01). Yahoo! en Español yielded the highest click-through rate (0.167%) and number of registrants (n = 267). The message framing and cultural targeting interaction was not significant. Contrary to hypotheses, loss-framed ads yielded a higher click-through rate than gain-framed ads (point estimate = 1.08, 95% CI 1.03 1.14, P = 0.004), and surface-targeted ads outperformed deep-targeted ads for clicks (point estimate = 1.20, 95% CI 1.13 1.28, P < .001), click-through rate (point estimate = 1.22, 95% CI 1.16 1.29, P < .001), and number of registrants (point estimate = 2.73, 95% CI 2.14 3.48, P < .001). ConclusionsOnline advertising can be an effective and cost-efficient strategy to reach and engage Spanish-speaking Latino smokers in an evidence-based Internet cessation program. Cultural targeting and smoking-relevant images may be important factors for banner ad design. Online advertising holds potential for Web-based cessation program implementation and research.